2022
DOI: 10.1038/s41562-021-01274-7
|View full text |Cite|
|
Sign up to set email alerts
|

Informative neural representations of unseen contents during higher-order processing in human brains and deep artificial networks

Abstract: A framework to pinpoint the scope of unconscious processing is critical to improve our models of visual consciousness. Previous research observed brain signatures of unconscious processing in visual cortex but these were not reliably identified. Further, whether unconscious content is represented in high-level stages of the ventral visual stream and linked parieto-frontal areas remains unknown. Using a within-subject, high-precision fMRI approach, we show that unconscious contents can be decoded from multivoxe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…However, while higher ventral brain regions also contain representations of invisible complex visual objects [9], fine-grained activity patterns within those regions differ between visible and invisible stimuli [10]. While some studies suggested higher visual cortex shares some representation between visible and invisible stimuli [10,11], unlike our experiments these studies used intact, complex images that did not explicitly require perceptual integration. These experiments therefore cannot rule out that neurons in higher category-selective regions merely respond to the presence of local features related to their preferred category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while higher ventral brain regions also contain representations of invisible complex visual objects [9], fine-grained activity patterns within those regions differ between visible and invisible stimuli [10]. While some studies suggested higher visual cortex shares some representation between visible and invisible stimuli [10,11], unlike our experiments these studies used intact, complex images that did not explicitly require perceptual integration. These experiments therefore cannot rule out that neurons in higher category-selective regions merely respond to the presence of local features related to their preferred category.…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence shows that some processing of visual objects occurs unconsciously [8]. Invisible stimuli activate higher object-selective brain areas [9][10][11] but responses are more variable [12,13] than during conscious perception. Activity patterns in ventral visual cortex measured while participants view complex images differ between visible and invisible stimuli [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additional details can be found in Mei et al (2022). (Mei et al, 2022b) Figure 1: Experimental paradigm. Example of the sequence of events within an experimental trial.…”
Section: Experimental Paradigmmentioning
confidence: 99%
“…Here we re-analysed fMRI data from a previous study (Mei et al, 2022b) in which participants (N = 7) underwent six fMRI sessions across six days while performing a discrimination task for animate and inanimate images presented very briefly and masked. In addition to multi-voxel pattern classification, we used model-based representational similarity analysis (RSA) to provide a fine-grained information-based approach to the neural representation of unconscious and conscious contents.…”
Section: Introductionmentioning
confidence: 99%
“…Although objective measures seem to align best with a scientific approach to consciousness (18, replicable, objective, e.g. see 19), they do require one to invoke a "Gold Standard of seeing" that in fact does not exist (20). Relatedly, they ignore the fact that subjective experience is central to the very definition of consciousness.…”
Section: Introductionmentioning
confidence: 99%